The Influence of Transformational Leadership, Psycological Well-Being on Employees' Performance with Organizational Citizen Behavior as Moderation - Fajar Setia Budi; Dian Afia Purwandari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the banking industry, the human aspect is essential in achieving the planned organization's vision, mission, and goals. The role of humans in the company is a pillar and a driver of organizational success. Transformational Leadership and Psychological well-being become a means to Improve Employee Performance. In addition, Organizational Citizen Behaviour is also a driver of Employee Performance in the organization. This study examined 222 banking employees in Indonesia using Structural Equation Modelling (SEM) analysis. The results of this study explain that transformational leadership and psychological well-being positively affect Organizational Citizenship Behaviour. In addition, Transformational Leadership, Psychological well-being has a positive relationship with Employee Performance, and Organizational Citizenship Behaviour positively impacts Employee Performance. The implication of this study is the need to examine different variables that can affect Employee Performance in addition to the variables in this study. This study examines the relationship between transformational leadership and employee performance with Organizational Citizenship Behaviour as a mediating variable. In addition, this research is an evaluation and correction material for management to see the influence of Transformational Leadership and Psychological well-being on employee performance and Organizational Citizenship Behaviour as mediation variables and can determine the right policies. This research can be used as material for analysis and learning about these variables to provide significant benefits to the community.